Improving the Memory through Singing Method of Children Ages 5 - 6 Years in Kindergarten Insan Pandhega - Meta Br Ginting (Faculty of Teacher Training and Education, Universitas Terbuka, 2019)
The problem in this study was that 48% of children had difficulty remembering their parents 'full names, 72% of children did not remember the full address of their residence, and 100% of children did not remember their parents' telephone numbers. This study aims to develop children's memory of their important personal identity through singing methods. This type of research is classroom action research by model Kemmis and Mc. Taggart. This research was carried out in the Kindergarten Insan Pandhega with a total subject of 25 children, consisting of 11 girls and 14 boys. The object of this research is the singing method. The technique of collecting children's memory data is done by non-formal test techniques, namely writing important information that describes the child's memory. Furthermore, the data is processed to obtain a memory percentage value of children categorized into: undeveloped, developing, developing well, developing very well. This study was successful if the memory of children who reached the criteria of developing well and developing very well reached more than 75%. The study was conducted in two cycles. Overall, the average memory of children in the first cycle which is in the well-developed and developing category is 36%. Whereas in the second cycle the average memory of children in the well-developed and very well-developed category was 80%.DOI: http://doi.org/10.31098/ijeiece.v1i2.44